Influence of yarn-hybridisation on the mechanical performance and thermal conductivity of composite laminates. Issue 3 (June 2022) - Dalfi, Hussein K; Al-Obaidi, Anwer; Selver, Erdem; Yousaf, Zeshan; Potluri, Prasad
Recently, advanced composite materials have been widely used in numerous applications due to their superior properties. However, their sensitivities to damages during impact loading event limits their usage. In this regards, the influence of yarn hybridisation on the mechanical and thermal performance of composite laminates have been studied using low velocity impact, compression after impact (CAI), flexural and thermal conductivity tests. Two types of composite laminates were manufactured using hybrid yarns (S-glass and polypropylene [PP]) and S-glass yarns through the combination of commingling and core-wrapping methods and converted to non-crimp cross-ply preforms for both laminates. C-scan tests and cross-section microscopy examinations were adopted to identify the damaged areas of impacted laminates and explain the damage failures, which occurred during impact loadings. Results revealed that the hybrid laminates displayed higher damage area reduction compared to glass composites. Although the hybrid composite laminates illustrated considerably lower compressive strength, their residual compressive strength (damage tolerance) was significantly higher than glass composites. Fractography analysis has illustrated that the new damage failure modes such as intra-yarn cracks have been observed in the hybrid yarns laminates. These damage modes have contributed for higher energy absorpsion leading to an enhancement of the damage tolerance of the hybrid laminates. Furthermore, the incorporation of PP fibres resulted in a reduction of thermal conductivity of hybrid laminates compared to pure glass laminates.